“Proyecto de parroquialización de la comunidad Shuar Tsurakú de la provincia de Pastaza” - Sharupi Juan, María Clara (2018)
This systematizing was made to identify and to know the reason why the project of the rural parochialization of the Tsurakú shuar community was not carried out; being a process that was almost reached. With this purpose, it was used a methodology of documentary review and participative action with three moments: First a description of the community, which consists of the socio-economic aspects and the basic services. Second, an analysis of the conceptual frame with the diverse theoretical positions and a review of the legal base that begins by recognizing Ecuador as "a constitutional State of rights and justice, a social, democratic, sovereign, independent, unitary, intercultural, multinational and secular State. It is organized as a republic and is governed using a decentralized approach" (Constitution, 2008). According to this, it regulates the rights in favor of the development and respect of cultural diversity. And the third contribution analyzed the participation of the basic organizations in making decisions, as well as the feedback of the State entities and their relation with the community organizations. That is why visits to the Autonomous Municipal Government of Pastaza were held, as well as meetings with the participants who were part of this process, and field visits to know the opinions of the community leaders and the vision of the people on what happened in order to be able to reach the elements of support to reconstruct the experience. The debate that presents this work has two fundamental problems: a) The lack of definition or overlaying of territorial borders and jurisdictions between adjacent sectors, and b) and the emergency of the offer of rural parochialization in Shuar territory.